ANALISIS PERUBAHAN PERKEMBANGAN PARIWISATA PADA STRUKTUR EKONOMI KOTA YOGYAKARTA SAAT NEW NORMAL - Dyah Wahyuning Tyas (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2022)
Covid-19 has affected the shift in the regional economic structure. This study aims to determine the shifting changes in the development of the tourism sector of Yogyakarta City during the new normal when Covid-19 pandemic and to determine the pattern of sectoral growth structure of the City of Yogyakarta. The analytical tools used in this research method are shift share analysis and Klassen typology analysis. The results of the shift share analysis conclude that the sub-sector of accommodation and food service activities in the tourism sector still has the opportunity to increase investment and technology development in order to realize a comparative advantage. While, the sectoral Klassen Typology analysis classify 17 categories consisting of sub-sectors of economic structure, each grouped into leading sectors, potential sectors, developing sectors, and underdeveloped sectors. As a result of Covid-19, the shift in the development of the tourism sector in the city of Yogyakarta leads to a potential sector. The value of its contribution to income (GRDP) has slowed. Therefore, government policies are needed on the development of the tourism sector. Nevertheless, Yogyakarta is still known as the City of Education, as evidenced by the education services sub-sector which is still the leading sector.Keywords: Shift Share; Klassen Typology Analysis; dan Tourism Sector